Inhibition of Immune Checkpoints and Vascular Endothelial Growth Factor as Combination Therapy for Metastatic Melanoma: An Overview of Rationale, Preclinical Evidence, and Initial Clinical Data - Ott, Patrick A.; Hodi, F. Stephen; Buchbinder, Elizabeth I. (Frontiers in Oncology, 2015)
The role of angiogenesis as a mediator of immune regulation in the tumor microenvironment has recently come into focus. Furthermore, emerging evidence indicates that immunotherapy can lead to immune-mediated vasculopathy in the tumor, suggesting that the tumor vasculature may be an important interface between the tumor-directed immune response and the cancer itself. The advent of immune checkpoint inhibition as an effective immunotherapeutic strategy for many cancers has led to a better understanding of this interface. TheWhile, the inhibition of angiogenesis through the targeting of VEGF has been used successfully for the treatment of cancer for many years,. Angiogenesis is a complex process and the anti-tumor activity of VEGF-directed therapy has been explained by several potential mechanisms including 1) direct effect on cancer cells, 2) alteration of vascular function and tumor blood flow, and 3) inhibition of vasculature growth in the tumor. Mechanisms the mechanisms behind its successexplaining much of the success of anti-VEGF therapy in patients remains of its anti-tumor activity remain poorly understood, with stabilization of the vasculature with improved chemotherapy drug delivery being highlightedan emphasis on combination therapies in many malignancies. Initial studies of More recently, with the advent of immune checkpoint inhibition as an effective immunotherapeutic strategy for many cancers, the role of angiogenesis as a mediator of immune regulation in the tumor microenvironment has come into focus. Furthermore, emerging evidence indicates that immunotherapy can lead to immune-mediated vasculopathy in the tumor, suggesting that the tumor vasculature may be an important interface between the tumor-directed immune response and the cancer itself.Ttheis complex relationship between angiogenesis, VEGF signaling and the immune system suggest that the combination of immune checkpoint blockade with angiogenesis inhibition has potential. While the majority of this work has been performed in metastatic melanoma, immunotherapy is rapidly showing promise in a broad range of malignancies and efforts to enhance immunotherapy will broadly impact the future of oncology. Here we review the preclinical rationale and initial clinical investigations of combined angiogenesis inhibition and immunotherapy/immune checkpoint inhibition as a potentially promising combinatorial approach for cancer treatment.